Transformasi Digital Heineken: Strategi Heineken Menghadapi Tantangan Pasar Global: Transformasi Digital Heineken: Strategi Heineken Menghadapi Tantangan Pasar Global - Stephanie; Soetam Rizky Wicaksono; Felicia (Universitas Sahid Surakarta, 2025)
This document analyzes Heineken's strategic position in the global market through PEST and SWOT approaches. The PEST analysis identifies the political, economic, social, and technological factors affecting Heineken's operations, showing that political and regulatory stability supports business expansion, even though economic challenges such as inflation can disrupt consumer purchasing power. From a social perspective, consumer preferences for healthy and environmentally friendly products and technological advances forced Heineken to adapt. The SWOT analysis highlights Heineken's strengths, including its global brand reputation and commitment to sustainability, as well as weaknesses related to high operating costs. Growth opportunities lie in the development of new products and digital technologies, while threats come from stiff competition. In conclusion, to maintain its position in the market, Heineken must continue to keep up with the development of digital transformation and innovate, as well as adjust marketing strategies according to changing consumer needs.